Strategi Dalam Mewujudkan Keluarga Sakinah i Kalangan Prajurit TNI Muslim - Saitul Mahtir Mahtir (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
One of the goals of marriage is to create a husband and wife who are full of love and affection and loyalty to obtain peace and tranquility (sakinah family). And to complete and realize the formation of a household as a sakinah family that is accompanied by full love and affection, it will be realized if all family members must be able to carry out their obligations properly, be it to God Almighty, themselves, family, society, the environment in general. . The type of research that the writer did was field research or field research with an empirical approach with qualitative writing methods. This type of research intends to study intensively about the current situation, the social interactions of individuals, groups, institutions and society. This research studied intensively the formation of a Muslim TNI sakinah family which was carried out by two former members of the TNI family in Banguntapan, Bantul, namely Mr. Kartono and Mr. H. Hartono. Based on research results and data obtained in the field and using a theoretical framework, the meaning of the sakinah family according to Mr. Kartono is the formation of individual religious characters in each individual family, having a strong mentality and practicing religion in their lives. Meanwhile, the meaning of a sakinah family according to Mr. H. Hartono's family is mutual understanding and carrying out the obligations and rights of husband and wife, practicing religious teachings and being able to see situations and conditions. The meaning of the sakinah family conveyed by the two does not have a significant difference, it's just that the rank and method are the fundamental differences. The essence of this meaning is that the foundation used is religion, as well as a strong mentality in all conditions encountered. Keywords: Family, Sakinah, TNI.